Drivers of rural exodus from Amazonian headwaters - Parry, L.; Day, B.; Amaral, S.; Peres, C.A. (2010)
Rural–urban migration can have both positive and negative environmental consequences for tropical forests. Rural residents exert pressure on the environment through farming, fishing, and forest extraction, yet conversely, protecting rural livelihoods is often the motivation for conserving large areas of threatened forest. This research examines rural settlement within the Brazilian Amazon to shed light on the drivers of on-going rural exodus and its environmental implications. Specifically, we examine the relative importance of public service provision and natural resources in determining settlement patterns along, and rural–urban migration from, eight rivers in road-less regions of the Brazilian Amazon. Data include biophysical, social, and economic variables that were assessed in 184 riverine settlements along rural–urban gradients up to 740 km from the nearest urban center. Settlements were smaller upstream, and lacked key services such as schools and healthcare. We found that clustering of rural populations close to urban centers reflects the high costs of living in remote areas, despite abundant natural resources which previously justified migration to headwaters. Impeded dry-season navigability and transport costs restricted the flow of goods and services to and from remote areas, and transaction costs of trade exchange were higher upstream. A lack of school access was the main motivation for rural–urban migration and the abandonment of remote riverine settlements. A key policy implication is that while education services could provide a powerful tool to stabilize and support rural populations, delivery is challenging in remote areas and may also encourage further rural–urban migration in the longer term. Furthermore, river-dwellers in remote areas rarely visited remote urban centers, presumably because these journeys are too costly. We examine the implications of our findings for anti-poverty subsidies and payment for ecosystem services and conclude that transport costs required to receive payment could encourage further depopulation of remote areas.